High-water-content silty clay unfired lightweight aggregate and preparation process thereof

By mixing quicklime with silty clay and hydration reaction and extrusion granulation, a high-water content silty clay fire-free light aggregate was prepared, which solved the problems of poor strength and poor water stability in road projects, and achieved efficient and economical roadbed reinforcement and improvement effects.

CN119774902APending Publication Date: 2025-04-08ANHUI HENGMEI TRANSPORTATION TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411969568.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve silty clay with high moisture content, resulting in poor strength, poor water stability and high engineering costs when used in highway projects.

Method used

By mixing quicklime with silty clay, hydration reaction and extrusion granulation treatment, a high moisture content silty clay is prepared. The process includes measuring the moisture content of silty clay, adding quicklime for breaking, then mixing with the gelling material and mechanically crushing, and finally preparing light aggregate through an extrusion granulation mechanism.

Benefits of technology

It achieves high strength and good water stability of silty clay light aggregates, and is suitable for reinforcement and improvement of silty clay roadbeds in plain areas lacking stone. At the same time, it reduces energy consumption and carbon emissions, and effectively reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774902A_ABST
    Figure CN119774902A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of artificial lightweight aggregates, in particular to a high-water-content silty clay unfired lightweight aggregate and a preparation process thereof.The preparation process comprises the following steps that S1, a silty clay sample is taken, the water content of the silty clay sample is measured, a certain proportion of quicklime is evenly scattered on silty clay, an alkaline environment is provided for subsequent hydration reaction, and the silty clay sample is prepared; carrying out scattering treatment by using a rotary cultivator, braising the materials for 24 hours, and adjusting the water content to obtain a first mixture; the preparation of the silty clay lightweight aggregate is realized by mixing the quick lime, the water, the silty clay and the cementing material and regulating and controlling the extrusion granulation process, the preparation method is simple and convenient, the energy consumption and the carbon emission can be greatly reduced, the silty clay is subjected to local and resource utilization, the conventional preparation by adopting a gravel material is replaced, and the preparation cost is reduced. The cost is effectively reduced, and the strength of the prepared silty clay lightweight aggregate is greatly improved compared with that of particles prepared by other baking-free methods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial light aggregate, and in particular to a high-moisture content silty clay unfired light aggregate and a preparation process thereof. Background Art

[0002] Fuyang City is located in the northwest of Anhui Province, north of the Huaihe River. The landforms are divided into two types according to their genesis: alluvial plains and erosion-alluvial plains. The surface and strata of the flooded slope plain are mainly composed of silty clay. The natural moisture content of silty clay in this plain area is usually between 20% and 35%, which brings great difficulty to construction. In addition, the clay content in the silty clay in this area is about 350-400g / kg, of which the montmorillonite content accounts for about 25-35% of the total minerals. It is a fine-grained soil with high moisture content and high clay content. The soil has high strength in a dry state, forms blocks, is not easy to disperse, quickly disintegrates under immersion conditions, and has extremely poor water stability. In highway engineering construction, it is usually necessary to dispose of the original soil to meet technical requirements.

[0003] At present, the improvement technologies for silty clay at home and abroad are mainly divided into three categories: physical improvement, chemical improvement and comprehensive improvement. Common chemical improvements are cement improvement and fly ash improvement. Cement used to reinforce high plastic clay will have problems such as inability to disperse and high dosage. The "Technical Specifications for Highway Pavement Base Construction" (JTG / T F20-2015) clearly states that "when cement is used for stabilization, the liquid limit of the stabilized material should not be greater than 40%, and the plasticity index should not be greater than 17." However, the plasticity index of silty clay in Fuyang City is usually between 18 and 30, so the effect of using cement alone is not good. Although the soil can be dispersed when using lime and fly ash for improvement, there is also the problem that the improved soil shows obvious brittle characteristics. Once shrinkage and temperature shrinkage cracking occur, it will have a serious impact on the structural stability of the soil. In addition, fly ash improvement also has the problem of low early strength and slow strength formation. If physical improvement is adopted, a large amount of high-quality fillers such as sand and gravel will be needed. However, the main terrain of Fuyang area is plains, and there is a shortage of stone materials, which need to be transported over long distances, resulting in high project costs.

[0004] If the sintering-free granulation technology can be used to comprehensively improve high-water content silty clay and prepare silty clay lightweight aggregate, it can not only be used as a roadbed filler or improver in areas where silty clay is widely distributed, but can also be used instead of stone in the concrete of non-structural components of buildings. The economic and environmental benefits are extremely significant. However, the research on granulation technology and lightweight aggregate for silty clay is still blank.

[0005] To this end, in response to the problems raised in the above background technology, those skilled in the art proposed a high-moisture content silty clay unburned lightweight aggregate and a preparation process thereof. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-water content silty clay unburned light aggregate and its preparation process to solve the various problems existing in the current silty clay treatment and solve the problem of aggregate shortage in plain areas. Through the dual effects of chemical reaction and extrusion granulation treatment, the density of silty clay light aggregate can be effectively improved, making it an ellipsoidal particle with higher performance. The produced light aggregate has the characteristics of higher strength and is suitable for reinforcing and improving silty clay roadbed in plain areas lacking stone.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The object of the present invention is to provide a process for preparing a high-water content silty clay unburned lightweight aggregate, comprising the following steps:

[0009] S1. Take a silty clay sample, measure its moisture content, evenly spread a certain proportion of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, stew it for 24 hours, and adjust the moisture content to obtain a first mixture;

[0010] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and uniformly mixing the slag powder, fly ash, cement, desulfurized gypsum and activator to obtain a cementitious material;

[0011] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 10 to 15 seconds, to obtain a second mixture;

[0012] S4, start the extrusion granulator, adjust the speed, and pour the second mixture prepared in step S3 after the speed is uniform, maintain a certain feeding speed, and preliminarily obtain a third mixture of silty clay aggregate;

[0013] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve, and place the sieved silty clay lightweight aggregate in a standard curing room. The curing time is 28 days, the curing temperature is 20±2° C., and the curing humidity is ≥95%. After the curing cycle, silty clay lightweight aggregate is obtained.

[0014] Furthermore, in step S3, the mass ratio of the cementitious material to the silty clay is 30:70 to 20:80.

[0015] Furthermore, the cement in step S2 is one of silicate cement and ordinary silicate cement, and the proportion of the cementitious material is 20-30% of the total mass.

[0016] Furthermore, in step S1, the addition ratio of quicklime is 1.5% to 2% of the mass of the silty clay, wherein the CaO content in the quicklime shall not be less than 70%;

[0017] At this time, quicklime mainly reacts chemically with water: CaO+H2O→Ca(OH)2. This reaction can not only absorb excess water from the silty clay, but also provide an alkaline environment and a large amount of Ca for subsequent hydration reactions. 2+ , promoting the formation of hydration products, which is the main reaction;

[0018] In addition, quicklime can also react with the active silica and alumina components in the clay to produce a hardening reaction. The reaction products are CSH and CAH, which can generate hydrate gel and break up the clay particles to make the clay "sand-like". However, this reaction is limited by the quicklime content and is therefore a secondary reaction.

[0019] The specific chemical reaction formula is as follows:

[0020] SiO2(active)+Ca(OH)2+H2O→CSH,

[0021] A12O3(active)+Ca(OH)2+H2O→CAH.

[0022] Furthermore, the slag powder in step S2 is Fuyang Huarun S95 grade F type II slag powder, the proportion of which is 50% to 60% of the mass of the cementitious material, wherein the CaO content in the slag powder is not less than 40%;

[0023] The fly ash is high-calcium fly ash, the CaO content in the fly ash is greater than 10%, and the mixing ratio thereof is 10% to 15% of the mass of the cementitious material.

[0024] Furthermore, the activator in step S2 is prepared from sodium carbonate and sodium sulfate, which are added to the cementitious material in the form of powder, with a mass ratio of 1:1 and an amount of 2% to 3% of the mass of the cementitious material; sodium carbonate is a strong base and weak acid salt, and its main component after hydrolysis and ionization is CO3 2- 、Na + and OH - , the chemical reaction formula is as follows:

[0025]

[0026] Among them, CO3 2- HCO3 is obtained during the hydrolysis of the solution - and OH - , OH - and Na + The combination produces NaOH, which raises the pH of the solution;

[0027] When sodium sulfate is combined with sodium carbonate alkali activator, it is generally combined with an alkali activator whose effective component is Ca(OH)2, such as Na2SO4 combined with cement, quicklime and slaked lime, which has excellent alkali activating effect;

[0028] In this mix, there are cement, quicklime and slag powder, which contain a large amount of CaO, which is hydrolyzed to generate Ca(OH)2, and the chemical reaction formula is as follows:

[0029] Ca(OH)2+2H2O+Na2SO4→CaSO4·2H2O+2NaOH

[0030] This reaction can increase the pH value of the Ca(OH)2 solution from 12.5 to 12.75, and the reaction activity and solubility of the newly generated NaOH are higher than those of Ca(OH)2.

[0031] Furthermore, the main component of the desulfurized gypsum in step S2 is CaSO4·2H2O, which is added to the cementitious material in the form of powder, and the amount of the two is 5% to 10% of the mass of the cementitious material. The role of the desulfurized gypsum is to supplement Ca 2+ With SO4 2- It can replace part of the cement, reduce costs and reduce hydration heat and shrinkage.

[0032] Furthermore, the rotation speed of the extrusion granulation in step S4 is adjusted to 35-40 rpm / min; and the feeding speed is adjusted to 0.3-0.4 kg / s.

[0033] Furthermore, in step S1, the moisture content is adjusted to a reasonable range, which not only satisfies that the moisture content of the silty clay is between the plasticity index and the liquid limit, but also satisfies the moisture content range of the material in the working range of the extruder during the extrusion process, and the final amount of water added takes the overlapping value of the moisture content.

[0034] A high-moisture content silty clay unfired light aggregate is prepared according to a preparation process of the high-moisture content silty clay unfired light aggregate.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The present invention realizes the preparation of silty clay light aggregate by adjusting the mixing of quicklime, water, silty clay and cementitious materials and the extrusion granulation process. The preparation method is simple and convenient, which can not only greatly reduce energy consumption and carbon emissions, but also utilize silty clay locally and as a resource, replacing the existing preparation using sand and gravel materials, effectively reducing costs, and the prepared silty clay light aggregate has greatly improved particle strength compared with other non-firing methods.

[0037] 2. The present invention uses the dual effects of chemical reaction and extrusion granulation treatment. First, the physical effect of extrusion is used to improve the density of clay silt and reduce the gaps between soil particles, making them ellipsoidal particles with higher performance; secondly, the lightweight aggregate formed by a series of chemical reactions in the hydration process of the cementitious material has the characteristics of high strength and is suitable for reinforcing and improving silty clay roadbeds or acting as stone materials in concrete for non-load-bearing structures.

[0038] The silty clay light aggregate prepared by the present invention has high uniformity in shape and performance, and the particle size of the produced particles can be accurately controlled. The particle size of the produced light aggregate can be adjusted according to the roller of the granulator, and the particle size range is between 2 and 30 mm, covering the particle size requirement range for stone in the pavement structure layer of highway engineering, so that the gradation of the light aggregate can be more accurately regulated, and the application scenarios are rich. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The present invention is a flow chart for preparing the high-water content silty clay unfired lightweight aggregate;

[0040] Figure 2 This is a physical picture of the fire-free lightweight aggregate of Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0043] The invention provides a preparation process of a high-moisture content silty clay unfired light aggregate, comprising the following steps: mixing high-moisture content silty clay and quicklime, reducing the moisture content while breaking up the silty clay, making the dispersed particles easy to mix with a cementitious material, adding the cementitious material after stewing, crushing and stirring evenly, and then extruding and granulating to obtain the silty clay unfired light aggregate.

[0044] In some specific embodiments, the mass ratio of the cementitious material to the silty clay is 30:70:~20:80. As a preferred technical solution of the present invention, the ratio of the amount of cementitious material added to the mass of silty clay can be any specific point value therebetween, such as 26:74, 21:79, etc., but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable, and will not be repeated here. In the present invention, the main components of silty clay are clay particles, silt particles and sand particles, wherein quicklime added to silty clay can not only quickly absorb water and release a large amount of heat, reduce the moisture content of silty clay, and facilitate the subsequent granulation process, but also act as a dispersant, making the clay particles in the silty clay "sanded", thereby reducing the plasticity index of the silty clay, so that the cementitious material can be mixed evenly with the silty clay.

[0045] Cementitious materials can not only undergo hydration reaction themselves, but the generated hydration products can also undergo physical and chemical reactions with clay particles in silty clay.

[0046] When cement is mixed with silty clay, the cement minerals undergo hydration reaction to form a cement stone skeleton, which constitutes part of the strength of the lightweight aggregate. Secondly, they undergo strong hydrolysis and hydration reactions with the water in the soil, while calcium hydroxide gel is released from the solution and other hydrates are formed. The surface of clay particles usually carries Na + and K + , Ca generated by cement hydration 2+ Will interact with Na in the soil + and K + The equivalent adsorption exchange is carried out, and as a result, the distance between soil particles is shortened, and a large number of soil particles form larger soil agglomerates. Since the CSH gel produced by cement hydration has strong adsorption activity, these larger soil agglomerates are further combined to form a chain structure of cement soil, closing the pores between soil agglomerates and thus forming a stable connection.

[0047] Fly ash is an industrial byproduct without hydration activity. Its main active ingredient is silicon aluminum oxide. The dense oxide shell on the surface of its spherical glass phase has good chemical stability at room temperature and pressure. Strong alkali is needed to break the Si-O-Si bond and Si-O-AI bond in it to release active substances. Under the action of strong alkali or activator, the bonds between crystals are broken, thereby reacting with OH - Chemical reactions occur to generate calcium silicate hydrate and calcium aluminate tetrahedral structures, which can undergo polycondensation reactions through common oxygen atoms to produce aluminosilicate gel with gelling properties; the chemical reaction formula is:

[0048] ≡Si-O-Si≡+3OH - →[SiO(OH)3] -

[0049] ≡AI-O-AI≡+4OH - →[AI(OH)4] -

[0050] ≡Si-O-AI≡+7OH - →[AI(OH)4] - +[SiO(OH)3] -

[0051] The early excitant provides a large amount of OH - The erosion of the silica-alumina glass phase structure in the volcanic ash decomposes a large amount of [SiO4] 4- and [AIO4] 5- tetrahedron.

[0052] Subsequently, the depolymerized [SiO4] 4- and [AIO4] 5- Between monomers and between them and the network-modified Ca ions 2+ , K + 、Na + The polycondensation reaction takes place to generate CSH and CAH gels; the chemical reaction formula is:

[0053] x C 2+ +y[SiO(OH)3]-+(zyx)H2O+(2x-y)OH - →C x -S y -H z (CSH gel)

[0054] 4Ca 2+ +2[AI(OH)4]-+6H2O+6OH - →C4-AH 13 (CAH gel)

[0055] These hydrate gels and clay particles together form a structural entity with a certain strength, thus constituting the strength of lightweight aggregate.

[0056] Slag powder contains high content of CaO, Al2O3 and SiO2, so it not only has a very high glass phase content, but also has high volcanic ash reactivity. Among them, Si-O-Si bond, AI-O-AI bond and Si-O-AI single bond and OH - The chemical reaction formula is similar to that of fly ash. In addition, it has a higher CaO content than fly ash, which is beneficial to the Ca 2+ With OH - The improvement has a significant effect, accelerating the formation of early hydration products.

[0057] In addition, the excess Ca(OH)2 reacts with CO2 in the air to form CaCO3 to fill the soil, further improving the strength of the lightweight aggregate.

[0058] In some specific embodiments, the cementitious material is cement, slag powder, fly ash, desulfurized gypsum and an activator.

[0059] In some specific embodiments, the rotation speed of the extrusion granulation is adjusted to 35-40rpm / min; the feeding speed is adjusted to 0.3-0.4kg / s. As a preferred technical solution of the present invention, the rotation speed of the extrusion granulation can be any specific point value between 35-40rpm / min, such as 35rpm / min, 36rpm / min or 38rpm / min, etc.; the feeding speed can be any specific point value between 0.3kg / s-0.4kg / s, such as 0.3kg / s, 0.35kg / s or 0.4kg / s, etc.; but it is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable, so they will not be repeated here. In the present invention, extrusion granulation can effectively improve the density of silty clay, making it into compact ellipsoidal particles, thereby improving the overall strength and stability. The preparation method is simple and convenient. It can not only greatly reduce energy consumption and carbon emissions, but also make on-site and resource-based utilization of silty clay silt, saving the transportation cost of sand and gravel materials. The prepared silty clay lightweight aggregate has greatly improved performance compared to particles prepared by other non-firing methods.

[0060] In some specific embodiments, the moisture content in the extrusion granulation process is 15-25%. As a preferred technical solution of the present invention, the moisture content in the extrusion granulation process can be any specific point value between 15% and 25%, such as 15%, 17%, 19%, 21%, 22% or 25%, etc., but is not limited to the listed values. Other values ​​not listed in the above numerical range are also applicable, and will not be repeated here.

[0061] In some specific embodiments, the particle size of the sieved silty clay light aggregate is between 2 and 30 mm. The particle size of the light aggregate is mainly related to the opening particle size of the roller mold of the extrusion granulator. The particle size range of the light aggregate for extrusion granulation can be any specific point value between 2 and 30%, such as 2%, 5%, 10%, 15%, 22% or 30%, etc., but it is not limited to the listed values. Other values ​​not listed in the above numerical range are also applicable, so they will not be repeated here. The granulation diameter of the double-roll extrusion granulator used in this experimental group is 10 mm.

[0062] In some specific embodiments, the particles formed after extrusion are subjected to standard curing, wherein the curing time is 28 days, the curing temperature is 20±2° C., and the curing humidity is ≥95%.

[0063] Further, the moisture content is adjusted to be greater than the plasticity index of the silty clay and less than the liquid limit of the silty clay, wherein the plasticity index = liquid limit - plastic limit, the plastic limit and the liquid limit are measured by a liquid-plastic limit combined determination method, and the liquid limit of the silty clay measured by the liquid-plastic limit combined determination method is 41.3, the plastic limit is 22.1, and the plasticity index is 19.2, while the moisture content in the extrusion granulation process is 15-25%, therefore, the moisture content of the first mixture should be controlled between 19.2 and 25.

[0064] The moisture content range is between the plasticity index (Ip) and the liquid limit (ωp), for example, it can be 22%, 23%, 25%, etc., but is not limited to the listed values. Other values ​​not listed in the above numerical range are also applicable and will not be repeated here.

[0065] The present invention uses the dual effects of chemical reaction and extrusion granulation treatment to effectively improve the density of silty clay lightweight aggregate, making it into ellipsoidal particles with higher performance. The produced lightweight aggregate has the characteristic of higher strength. It can not only be used as a roadbed filler or improver in areas where silty clay is widely distributed, but also can be used in concrete of non-structural components of buildings instead of stone. The economic and environmental benefits are extremely significant.

[0066] like Figure 1-2 As shown, the invention is further described below through specific embodiments.

[0067] Example 1

[0068] A preparation process of high-water content silty clay unburned lightweight aggregate, comprising the following steps:

[0069] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 80 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 20%, thereby obtaining a first mixture;

[0070] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and evenly mixing 560g of slag powder, 120g of fly ash, 220g of cement, 70g of gypsum and 30g of activator to obtain a cementitious material;

[0071] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 10 seconds, to obtain a second mixture;

[0072] S4, start the extrusion granulator, adjust the speed to 36 rpm / min, and pour the second mixture prepared in step S3 after the speed is uniform, with a feeding rate of 0.4 kg / s, to preliminarily obtain a third mixture of silty clay aggregate;

[0073] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0074] Example 2

[0075] A preparation process of high-water content silty clay unburned lightweight aggregate comprises the following steps:

[0076] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 80 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 21%, thereby obtaining a first mixture;

[0077] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and uniformly mixing 500 g of slag powder, 100 g of fly ash, 300 g of cement, 80 g of gypsum and 20 g of activator to obtain a cementitious material;

[0078] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 12 seconds, to obtain a second mixture;

[0079] S4, start the extrusion granulator, adjust the speed to 37 rpm / min, and pour the second mixture prepared in step S3 after the speed is uniform, with a feeding rate of 0.35 kg / s, to preliminarily obtain a third mixture of silty clay aggregate;

[0080] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0081] Example 3

[0082] A preparation process of high-water content silty clay unburned lightweight aggregate comprises the following steps:

[0083] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 80 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 22%, thereby obtaining a first mixture;

[0084] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and evenly mixing 520 g of slag powder, 150 g of fly ash, 200 g of cement, 100 g of gypsum and 30 g of activator to obtain a cementitious material;

[0085] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 15 seconds, to obtain a second mixture;

[0086] S4, start the extrusion granulator, adjust the speed to 36 rpm / min, and pour the second mixture prepared in step S3 after the speed is uniform, with a feeding rate of 0.40 kg / s, to preliminarily obtain a third mixture of silty clay aggregate;

[0087] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0088] Example 4

[0089] A preparation process of high-water content silty clay unburned lightweight aggregate comprises the following steps:

[0090] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 60 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 25%, thereby obtaining a first mixture;

[0091] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and uniformly mixing 580g of slag powder, 130g of fly ash, 220g of cement, 50g of gypsum and 20g of activator to obtain a cementitious material;

[0092] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 12 seconds, to obtain a second mixture;

[0093] S4, start the extrusion granulator, adjust the speed to 36 rpm / min, and pour the second mixture prepared in step S3 after the speed is uniform, with a feeding rate of 0.40 kg / s, to preliminarily obtain a third mixture of silty clay aggregate;

[0094] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0095] Control group 1

[0096] A preparation process of high-water content silty clay unburned lightweight aggregate, comprising the following steps:

[0097] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 80 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 30%, thereby obtaining a first mixture;

[0098] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and evenly mixing 560g of slag powder, 120g of fly ash, 220g of cement, 70g of gypsum and 30g of activator to obtain a cementitious material;

[0099] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 10 seconds, to obtain a second mixture;

[0100] S4, start the extrusion granulator, adjust the speed to 36 rpm / min, and pour the second mixture prepared in step S3 after the speed is uniform, with a feeding rate of 0.4 kg / s, to preliminarily obtain a third mixture of silty clay aggregate;

[0101] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0102] Control group 2

[0103] A preparation process of high-water content silty clay unburned lightweight aggregate, comprising the following steps:

[0104] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 80 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 20%, thereby obtaining a first mixture;

[0105] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and uniformly mixing 600 g of slag powder, 150 g of fly ash, 150 g of cement, 70 g of gypsum and 30 g of activator to obtain a cementitious material;

[0106] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 10 seconds, to obtain a second mixture;

[0107] S4, start the extrusion granulator, adjust the speed to 36 rpm / min, and pour the second mixture prepared in step S3 after the speed is uniform, with a feeding rate of 0.4 kg / s, to preliminarily obtain a third mixture of silty clay aggregate;

[0108] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0109] Control group 3

[0110] A preparation process of high-water content silty clay unburned lightweight aggregate comprises the following steps:

[0111] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 80 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 20%, thereby obtaining a first mixture;

[0112] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and evenly mixing 560g of slag powder, 120g of fly ash, 220g of cement, 70g of gypsum and 30g of activator to obtain a cementitious material;

[0113] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 10 seconds, to obtain a second mixture;

[0114] S4, start the extrusion granulator, adjust the speed to 50 rpm / min, and pour the second mixture prepared in step S3 after the speed is uniform, with a feeding rate of 0.50 kg / s, to preliminarily obtain a third mixture of silty clay aggregate;

[0115] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0116] Control group 4

[0117] A preparation process of high-water content silty clay unburned lightweight aggregate, comprising the following steps:

[0118] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 80 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 20%, thereby obtaining a first mixture;

[0119] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and evenly mixing 560g of slag powder, 120g of fly ash, 220g of cement, 70g of gypsum and 30g of activator to obtain a cementitious material;

[0120] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 10 seconds, to obtain a second mixture;

[0121] S4, start the extrusion granulator, adjust the speed to 20rpm / min, pour the second mixture prepared in step 3 after the speed is uniform, and add the feed rate to 0.25kg / s to preliminarily obtain a third mixture of silty clay aggregate;

[0122] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0123] Control group 5

[0124] A preparation process of high-water content silty clay unburned lightweight aggregate, comprising the following steps:

[0125] S1. Take 4000 g of silty clay sample, measure its moisture content, evenly spread 80 g of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, and stew it for 24 hours to adjust its moisture content to 20%, thereby obtaining a first mixture;

[0126] S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and evenly mixing 560g of slag powder, 120g of fly ash, 220g of cement, 70g of gypsum and 30g of activator to obtain a cementitious material;

[0127] S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 5 seconds, to obtain a second mixture;

[0128] S4, start the extrusion granulator, adjust the speed to 36 rpm / min, and pour the second mixture prepared in step S3 after the speed is uniform, with a feeding rate of 0.4 kg / s, to preliminarily obtain a third mixture of silty clay aggregate;

[0129] S5. Pass the third mixture obtained in step S4 through a 6 mm square hole sieve to sieve out the unformed silty clay light aggregate to obtain formed silty clay light aggregate. Place the silty clay light aggregate in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

[0130] The bulk density, water absorption, compressive strength and cylinder compressive strength of the silty clay unburned lightweight aggregate prepared in the embodiment and the comparative example were tested using GB / T1743-2010 “Lightweight aggregate and its test methods”. The results are shown in Table 1.

[0131] Table 1 Performance of silty clay unburned lightweight aggregate in Examples and Comparative Examples

[0132]

[0133] As shown in Table 1, in Examples 1, 2, 3 and 4, cement, fly ash, slag powder, gypsum powder and activator are appropriately adjusted within the recommended ratio range. It can be seen from Example 1 and Example 2 that when the cement content increases and the slag powder and fly ash content decreases, the compressive strength of the single particle of silty clay lightweight aggregate increases slightly, but it can be seen from Example 1 and Comparative Example 2 that when the cement content is reduced from 220g to 150g in Comparative Example 2, which is lower than the recommended content of 200g to 300g, the granulation rate does not change significantly, but the 28d single particle compressive strength is greatly reduced from 2.92MPa to 1.61MPa. This is because the proportion of effective hydrates such as tricalcium silicate and dicalcium silicate in the cement clinker components increases, and these clinkers react with the water in the soil to produce hydrated calcium silicate, calcium hydroxide gel and other hydration products. These hydration products not only form strength themselves, but also form stable connections between soil masses through hydrate gel, and finally improve the strength of the particles through carbonation. Therefore, the basic rule is that as the cement content continues to increase, the compressive strength and cylinder pressure strength of the 28d particles increase, and the bulk density also increases accordingly, but the cost also increases accordingly.

[0134] Example 3 is based on Example 1. The fly ash mass is increased by 30g and the slag powder dosage is reduced by 40g. The 28d single particle compressive strength decreases slightly. This is because the main components of slag powder are active calcium oxide and silicon oxide, while the main components of fly ash are aluminum oxide and silicon oxide. Slag powder can produce a large amount of hydration products under alkaline conditions, among which Ca 2+ With OH - It can participate in alkali-induced reaction and hydration reaction in large quantities, thereby improving the overall strength of lightweight aggregate.

[0135] Example 4, Comparative Example 1 Compared with Example 1, the moisture content during the granulation process increased from 20% to 25%, and then increased to 30% outside the recommended moisture content range, and the granulation rate decreased from 91% to 81%, that is, the extrusion granulation within the 25% moisture content range can still maintain a granulation rate of more than 80%. However, when it was increased to 30%, the granulation rate dropped significantly to 62%. This is because the plasticity index of clay is too high when it is too wet, and it is easy to stick to the roller. A large amount of clay adheres to the double rollers of the granulator, affecting the normal granulation work. Therefore, controlling the moisture content is beneficial to improving the granulation rate of lightweight aggregate.

[0136] Comparative Examples 3 and 4 increase the granulator speed, the material dumping speed, and slow down the granulator speed and material dumping speed for Example 1. It can be seen from the test results that the effect of significantly increasing the granulator speed and material dumping speed on the granulation rate is much greater than slowing down the speed and material dumping speed, but both are significantly lower than the granulation rate of granulated particles within the normal granulator speed and material dumping speed range. This is because when the material dumping speed is too fast, a large amount of the mixture accumulates between the double rollers and enters the discharge port without being fully squeezed. The light aggregate prepared in this way not only has a low ball formation rate, but the performance of the light aggregate is also significantly lower than that of the formed particles at normal speed. When the granulator speed is too slow, it will also have a negative correlation with the compaction of the particles, but the impact on the performance of the granulation and light aggregate particles is lower than when the speed is too fast.

[0137] In Comparative Example 5, the stirring and crushing time is reduced from 10 s to 5 s during the secondary crushing in Example 1. At this time, the second mixture is not fully mixed, and the clay particles are fully broken up and fully combined with the cementitious material before entering the extrusion granulation process. At this time, there are many uncombined soil clumps in the internal structure of the lightweight aggregate. These soil clumps are destroyed when subjected to force, resulting in a significant reduction in the strength of the lightweight aggregate.

[0138] The present invention realizes the preparation of silty clay light aggregate by regulating the mixing of quicklime, water, silty clay and cementitious materials and the extrusion granulation process. The preparation method is simple and convenient, which can not only greatly reduce energy consumption and carbon emissions, but also make local and resourceful use of silty clay, replace the existing preparation method using sand and gravel materials, effectively reduce costs, and the prepared silty clay light aggregate has greatly improved particle strength compared with other particles prepared by non-firing methods.

[0139] The present invention adopts the dual effects of chemical reaction and extrusion granulation treatment. Firstly, the density of clay silt is improved through the physical effect of extrusion, and the gaps between soil particles are reduced, so that it becomes ellipsoidal particles with higher performance; secondly, the lightweight aggregate formed by a series of chemical reactions in the hydration process of the cementitious material has the characteristics of high strength, and is suitable for reinforcing and improving silty clay roadbed or acting as stone for concrete used in non-load-bearing structures.

[0140] The silty clay light aggregate prepared by the present invention has high uniformity in shape and performance, and the particle size of the produced particles can be accurately controlled. The particle size of the produced light aggregate can be adjusted according to the roller of the granulator, and the particle size range is between 2 and 30 mm, covering the particle size requirement range for stone in the pavement structure layer of highway engineering, so that the gradation of the light aggregate can be more accurately regulated, and the application scenarios are rich.

[0141] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing high-water content silty clay unburned lightweight aggregate, characterized in that: The following steps are involved: S1. Take a silty clay sample, measure its moisture content, evenly spread a certain proportion of quicklime on the silty clay to provide an alkaline environment for subsequent hydration reaction, break it up with a rotary tiller, stew it for 24 hours, and adjust the moisture content to obtain a first mixture; S2, mechanically crushing the silty clay after the stewing process in step S1 for the first time, and uniformly mixing the slag powder, fly ash, cement, desulfurized gypsum and activator to obtain a cementitious material; S3, uniformly dispersing the gelling material obtained in step S2 in the silty clay for hydration reaction, and performing a second mechanical crushing by a mixer with a rotary crushing device, the second mechanical crushing time being 10 to 15 seconds, to obtain a second mixture; S4, start the extrusion granulator, adjust the speed, and pour the second mixture prepared in step S3 after the speed is uniform, maintain a certain feeding speed, and preliminarily obtain a third mixture of silty clay aggregate; S5. The third mixture prepared in step S4 is sieved with a sieve gap size of 2 to 30 mm, and unformed silty clay light aggregate is sieved out to obtain formed silty clay light aggregate. The silty clay light aggregate is placed in a standard curing room for 28 days at a curing temperature of 20±2° C. and a curing humidity of ≥95%. After the curing cycle, silty clay light aggregate is obtained.

2. The process for preparing the high-moisture content silty clay unburned lightweight aggregate according to claim 1, characterized in that: The mass ratio of the cementitious material to the silty clay in step S3 is 30:70 to 20:

80.

3. The process for preparing the high-moisture content silty clay unfired lightweight aggregate according to claim 1, characterized in that: The cement in step S2 is one of silicate cement and ordinary silicate cement, and the proportion of the cementitious material is 20-30% of the total mass.

4. The process for preparing the high-moisture content silty clay unfired lightweight aggregate according to claim 1, characterized in that: In step S1, the addition ratio of quicklime is 1.5% to 2% of the mass of the silty clay, wherein the CaO content in the quicklime shall not be less than 70%; At this time, quicklime mainly reacts chemically with water: CaO+H2O→Ca(OH)2. This reaction can not only absorb excess water from the silty clay, but also provide an alkaline environment and a large amount of Ca for subsequent hydration reactions. 2+ , promoting the formation of hydration products, which is the main reaction; In addition, quicklime can also react with the active silica and alumina components in the clay to produce a hardening reaction. The reaction products are CSH and CAH, which can generate hydrate gel and break up the clay particles to make the clay "sand-like". However, this reaction is limited by the quicklime content and is therefore a secondary reaction. The specific chemical reaction formula is as follows: SiO2(active)+Ca(OH)2+H2O→CSH, AI2O3(active)+Ca(OH)2+H2O→CAH.

5. The process for preparing the high-moisture content silty clay unfired lightweight aggregate according to claim 1, characterized in that: The slag powder in step S2 is Fuyang Huarun S95 grade F type II slag powder, the proportion of which is 50% to 60% of the mass of the cementitious material, wherein the CaO content in the slag powder is not less than 40%; The fly ash is high-calcium fly ash, the CaO content in the fly ash is greater than 10%, and the mixing ratio thereof is 10% to 15% of the mass of the cementitious material.

6. The process for preparing high-moisture content silty clay unfired lightweight aggregate according to claim 1, characterized in that: The activator in step S2 is prepared from sodium carbonate and sodium sulfate, and is added to the cementitious material in the form of powder, with a mass ratio of 1:1 and an amount of 2% to 3% of the mass of the cementitious material; Sodium carbonate is a strong base and weak acid salt. Its main component after hydrolysis and ionization is CO3 2- 、Na + and OH - , the chemical reaction formula is as follows: Among them, CO3 2- HCO3 is obtained during the hydrolysis of the solution - and OH - , OH - and Na + The combination produces NaOH, which raises the pH of the solution; When sodium sulfate is combined with sodium carbonate alkali activator, it is generally combined with an alkali activator whose effective component is Ca(OH)2, such as Na2SO4 combined with cement, quicklime and slaked lime, which has excellent alkali activating effect; In this mix, there are cement, quicklime and slag powder, which contain a large amount of CaO, which is hydrolyzed to generate Ca(OH)2, and the chemical reaction formula is as follows: Ca(OH)2+2H2O+Na2SO4→CaSO4·2H2O+2NaOH This reaction can increase the pH value of the Ca(OH)2 solution from 12.5 to 12.75, and the reaction activity and solubility of the newly generated NaOH are higher than those of Ca(OH)2.

7. The process for preparing high-moisture content silty clay unfired lightweight aggregate according to claim 1, characterized in that: The main component of the desulfurized gypsum in step S2 is CaSO4·2H2O, which is added to the cementitious material in the form of powder. The amount of the two is 5% to 10% of the mass of the cementitious material. The role of the desulfurized gypsum is to supplement Ca 2+ With SO4 2- It can replace part of the cement, reduce costs and reduce hydration heat and shrinkage.

8. The process for preparing high-moisture content silty clay unfired lightweight aggregate according to claim 1, characterized in that: The rotation speed of the extrusion granulation in step S4 is adjusted to 35-40 rpm / min; the feeding speed is adjusted to 0.3-0.4 kg / s.

9. The process for preparing high-water content silty clay unfired lightweight aggregate according to claim 1, characterized in that: In step S1, the moisture content is adjusted to a reasonable range, which must satisfy both that the moisture content of the silty clay is between the plasticity index and the liquid limit and that the moisture content of the material in the working range of the extruder during the extrusion process is within the range, and the final amount of water added is the overlapping value of the moisture content.

10. A high-water content silty clay unburned lightweight aggregate, characterized in that: The material is prepared according to the process for preparing high-moisture content silty clay unburned lightweight aggregate according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation process of silt aggregate

    CN118702427A

  • Soil solidifying agent

    CN1730836A